2019
DOI: 10.1002/ppp3.10077
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of European ash (Fraxinus excelsior) saplings to larval feeding by the emerald ash borer (Agrilus planipennis)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Interestingly, the diversity of secoiridoids in F. excelsior identified here and in bark extracts is greater than that reported in green and white ash species native to North America 2,44,52,54 . F. excelsior may be more tolerant to EAB than Fraxinus species native to North America as recently reported 56 , consistent with complementary studies showing that adult A. planipennis has a much greater feeding preference for leaves of green, white and black ash compared to Manchurian and European ash 57 . It remains to be determined whether F. excelsior in European forests is more or less tolerant to A. planipennis than F. pennsylvanica 24 .…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the diversity of secoiridoids in F. excelsior identified here and in bark extracts is greater than that reported in green and white ash species native to North America 2,44,52,54 . F. excelsior may be more tolerant to EAB than Fraxinus species native to North America as recently reported 56 , consistent with complementary studies showing that adult A. planipennis has a much greater feeding preference for leaves of green, white and black ash compared to Manchurian and European ash 57 . It remains to be determined whether F. excelsior in European forests is more or less tolerant to A. planipennis than F. pennsylvanica 24 .…”
Section: Discussionsupporting
confidence: 89%
“…A key focus of ongoing research is the potential protection provided by the dominance of F. excelsior in GB. Experimental studies have demonstrated partial resistance of F. excelsior to EAB under laboratory conditions (Showalter et al, 2020). In the field, this resistance may make it harder for the pest to establish and slow population growth, thereby providing a longer window for control of new outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potentially important differences in the biophysical environment that could affect this conclusion. GB winters are mild and so may be more conducive to a longer development period enabling completion of life stages into late autumn; however, this effect may be restricted by photoperiod which can also affect the timing of winter dormancy (Saunders, 2020); many of our trees are weakened by ADB with unknown impact on EAB behaviour and development (Dearborn et al, 2018;Showalter et al, 2020); the spatial distribution, mix with other species, and planting density may impact active flight distances; and parasitoids already present in the environment may attack EAB (Bauer et al, 2015). In addition, based on the variation in reported degree days at emergence and at peak flight activity, the link between degree day accumulation and behaviour does not appear to be as strong as reported for many other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, current experiments have shown that saplings of F. excelsior are much less susceptible than F. nigra Marsh. to A. planipennis (Showalter et al 2019). Fraxinus excelsior is rare in the Moscow region and other regions of northern and central Russia.…”
Section: Introductionmentioning
confidence: 99%